Targeting B-raf/MEK signaling in melanocytic carcinoma using HPLC-MS/MS characterized metabolites from Valeriana wallichii Rhizome - Charushila V. Balikai; Raviraj M. Kulkarni; Kiran Thabaj; Shankar Gharge; Rohini S. Kavalapure; Shyam S. Desai (Pharmacological Research - Modern Chinese Medicine)
Valeriana wallichii (mǎ lù róng cǎo), a traditional medicinal herb native to southwestern China, holds promise as a source of novel anticancer agents. This study explores its therapeutic potential against A375 human melanoma cells through an integrated in silico, in vitro pharmacological approach. High-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) profiling of the ultrasonication-assisted hydroalcoholic extract identified key phytoconstituents, notably chlorogenic acid and quinic acid. Network pharmacology analysis linked these metabolites to critical signaling pathways involved in skin cancer progression, particularly the MAPK, PI3K-Akt, and Ras pathways. Target prediction and protein interaction networks further revealed modulation of key nodes such as BRAF and MEK. Molecular docking highlighted strong binding affinities of chlorogenic acid at the ATP-binding domains of both BRAF (CYS532, ASP594, LYS483, GLY534) and MEK (SER150, ALA95), with interaction energies comparable to reference inhibitors dabrafenib and DS03090629. Molecular dynamics simulations (100 ns) confirmed the stable occupation of these active sites by chlorogenic acid, supporting its potential as a dual BRAF/MEK inhibitor. ADME predictions revealed favorable drug-like properties for the major compounds. In vitro cytotoxicity assays on A375 melanoma cells demonstrated significant antiproliferative effects of the V. wallichii extract obtained via ultrasonication (IC₅₀ = 172.8 ± 1.07 μg/mL), with scanning electron microscopy indicating enhanced cell membrane disruption, likely due to improved bioactive extraction efficiency. Collectively, these findings underscore the potential of Valeriana wallichii rhizome metabolites, particularly chlorogenic acid, as multitargeted therapeutic agents in melanocytic carcinoma. This study provides scientific validation for the traditional use of V. wallichii in Chinese medicine and lays the groundwork for its development as a modern pharmacological intervention targeting BRAF/MEK signaling in skin cancer.